AB1077-HPR Fibromyalgia Syndrome: Nurse Case Management for A Structured Patient Pathway. (15th July 2016) - El Aoufy, K.; Piemonte, G.; Mikhaylova, S.; Rasero, L.; Maddali Bongi, S.
Abstract : Background: Fibromyalgia Syndrome (FMS) is a common, potentially disabling, chronic disorder that is defined by widespread pain, often accompanied by fatigue and sleep disturbance, cognitive and somatic symptoms. Fibromyalgia continues to present a challenge for healthcare professionals (HCPs) because of the lack of a clear patient pathway. Nurses' role need to be better defined. Objectives: Our aim is to investigate the presence of correlations between clinical and clinimetric parameters and Fibromyalgia Scale (FS) assessed by 2011 ACR criteria, in order to define which parameters should have priority in the construction of a care plan for FMS patients, as well as outline a role for nurses specifically designed for FMS patients. Methods: 168 patients (155 women and 13 men; age MEAN±DS 54.50 ± 12.32) were evaluated for clinical and demographic parameters: age, sex, disease duration, year of diagnosis and latency of the disease. They were assessed by FS, which is divided into Wide Pain Index and Symptoms Score, and gives a total score of severity (FS with range 0–31 and cut off ≥13). They were also assessed for pain and sleep (Numeric Rating Scale Pain and NRS Sleep), Regional Pain Scale (RPS), disability (Fibromyalgia Impact Questionnaire and Health Assessment Questionnaire), mood disorders (Hospital Anxiety and Depression Scale), sleep quality (Numeric Rating Scale Sleep), fatigue (Functional Assessment of Chronic Illness Therapy- Fatigue) and quality of life (Short Form-36). Results: FS is significantly and positively correlated with HADS-D for depression, HADS-A anxiety, NRS for pain, FIQ, HAQ and FACIT-F (p<0.01) and Tender-Points (p<0.05), it is also significantly and negatively correlated with the NRS for sleep quality, SF 36 all subscales, and ISF (p: <0.05) and ISM (p: <0.01). At linear regression model, FS is significantly and independently associated with RPS, FACIT-F and with SF_36_RE, that together explain the variability of FS in 96% (88.7%; 5.4%;1.9% respectively). Conclusions: It would be desirable, therefore, the use of FS scale in everyday clinical practice, thus allowing nurses to assess FMS patients and plan their clinical and therapeutic pathway, together with the rheumatologist. Our results confirm that important aspects to be treated in FMS patients are quality of life, pain and fatigue, they are considered as independent predictors for FS. Thus, they explain 96% of FS score variability. In this context nurses' role is crucial since FMS most common symptoms seem to be adequately treated with a multimodal and holistic approach and with interventions tailored to the individual. Thus, we propose a Case Manager Nurse (CMN) that should set up and coordinate a multidisciplinary approach aiming at improving FMS patients' QoL and self-perceived health status. References: Hadker N, Garg S, Chandran AB et al. Primary care physicians' perceptions of the challenges and barriers in the timely diagnosis, treatment and management of fibromyalgia. Pain Res Manag 2011; 16: 440–4. Wolfe F, Clauw DJ, Fitzcharles MA et al. Fibromyalgia criteria and severity scales for clinical and epidemiological studies: a modification of the ACR Preliminary Diagnostic Criteria for Fibromyalgia. 2011 38:1113–22. doi: 10.3899/jrheum.100594. Epub 2011 Feb 1 Carville S. Arendt-Nielsen S. Bliddal H. EULAR evidence based recommendations for the management of fibromyalgia syndrome. Ann Rheum Dis 2008; 67: 536–41. Disclosure of Interest: None declared